Effects of Extracardiac Factors in Signal-Averaged Electrocardiography-measured Late Potentials from Early Anterior Myocardial Infarction in Intensive Cardiac Care Unit - Christopher Surya Suwita; Sally Aman Nasution; Muhadi Muhadi; Juferdy Kurniawan (Interna Publishing, 2020)
Background: one modality that can predict ventricular arrhythmias after myocardial infarction (MI), particularly anterior MI, is signal-averaged electrocardiogram (SA-ECG), through the detection of late potentials (LP) which is a substrate for ventricular arrhythmias. Extracardiac factors, which are also risk factors for MI, such as hypertension, diabetes, dyslipidemia, and obesity, are apparently associated with post-MI ventricular arrhythmias, which in turn may be correlated with LP. This study aims to determine the effect of extracardiac risk factors on LP incidence in anterior MI patients treated in the intensive cardiac care unit (ICCU). Methods: this was a cross-sectional study in which 80 subjects with anterior MI during the period of December 2018-2019 underwent SA-ECG examination. The medical history and extracardiac risk factors were recapitulated, and then the SA-ECG data was taken from either direct examination or ICCU patients' database in that period. This study used multivariate analysis with logistic regression test. Results: the most common factors found were hypertension (70.00%), followed by dyslipidemia (56.25%), diabetes (46.25%), and obesity (38.75%). Obesity and dyslipidemia are extracardiac factors with the two biggest roles in the prevalence of LP. However, from additional analysis, we found that diabetes with acute hyperglycemia also had immense influence on the occurrence of LP. The OR for diabetes with acute hyperglycemia, obesity, and dyslipidemia were 4.806 (IK95% 0.522-44.232), 4.291 (IK95% 0.469-39.299), and 3.237 (IK95% 0.560-18.707). However, the association is not statistically significant. Conclusion: patients with anterior MI who suffer from diabetes with hyperglycemia in admission, obesity, and dyslipidemia have a potentially higher LP prevalence, despite statistical insignificance. To increase the prognostic value of SA-ECG, serial examinations are needed during hospitalization.